2009
DOI: 10.1108/13527600910953900
|View full text |Cite
|
Sign up to set email alerts
|

Quality management: a cross‐cultural perspective

Abstract: PurposeThe aim of this paper is to present the results of a survey administered across 23 countries that examines quality priorities, practices and performance by adopting Hofstede's national cultural framework. The purpose of this study is to test the validity of the “culture‐specific” argument as an explanatory construct for explaining quality management.Design/methodology/approachData were collected in 2006 as part of the IV iteration of the International Manufacturing Strategy Survey. The methodology invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 35 publications
(32 reference statements)
2
16
0
Order By: Relevance
“…Mathews et al 2001;Vecchi and Brennan, 2009), based on which it could be argued that the Spanish business culture might be linked to the consistent way that the EFQM is adopted in Spain. In this vein and inspired by Mathews et al (2001), one may reason that the strong uncertainty avoidance dimension of the Spanish national culture could explain why organizations adopt the EFQM as a unique model: by interpreting criteria as rules (or established codes of behavior) that should be followed, they may be trying to minimize the risk of failure.…”
Section: Integrated Use Of Best Practicesmentioning
confidence: 99%
“…Mathews et al 2001;Vecchi and Brennan, 2009), based on which it could be argued that the Spanish business culture might be linked to the consistent way that the EFQM is adopted in Spain. In this vein and inspired by Mathews et al (2001), one may reason that the strong uncertainty avoidance dimension of the Spanish national culture could explain why organizations adopt the EFQM as a unique model: by interpreting criteria as rules (or established codes of behavior) that should be followed, they may be trying to minimize the risk of failure.…”
Section: Integrated Use Of Best Practicesmentioning
confidence: 99%
“…The increased complexity of today's business environment and heightened international competition make it necessary for organizations to improve quality performance by aligning their quality practices in their attempt to capitalise on all possible traditional and non-traditional sources of competitive advantage (Vecchi and Brennan 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In terms of national cultural models, most previous studies refer to Hofstede's dimensions (e.g. Mathews et al, 2001;Lagrosen, 2002;Flynn and Saladin, 2006;Jung et al, 2008;Vecchi and Brennan, 2009). The studies do not fully agree about which of Hofstede's cultural dimensions has the greatest influence on QM, but they make it clear that power distance and uncertainty avoidance play significant roles in the differences between QM perception and practices (Mathews et al, 2001).…”
Section: Quality Management In Cross-cultural Settingsmentioning
confidence: 99%
“…At the national level, many studies have shown that national culture affects the perceptions of QM values, and the use of QM techniques and tools (e.g. Mathews et al, 2001;Flynn and Saladin, 2006;Vecchi and Brennan, 2009). Mathews et al (2001) studied the motivation for QM adoption, the use of QM techniques and tools, and the results of QM in the UK, Finland and Portugal.…”
Section: Quality Management In Cross-cultural Settingsmentioning
confidence: 99%
See 1 more Smart Citation